Hubungan Tingkat Keterampilan Mengajar Guru Perempuan pada Bidang Studi Pendidikan Agama Islam terhadap Hasil Belajar Peserta Didik di SMP Muhammadiyah Limbung Kec. Bajeng Kab. Gowa - Nurhikmah Nurhikmah (AN-NISA, 2018)
This research aimed to find out the teaching skill of Islamic Religious Education teachers wowen , the result of the students’ learning outcome, and the relation between the teachers’ women skill andthe students’ learning outcome at Muhammadiyah junior high school Limbung, Bajeng District, Gowa Regency. The purpose of this study was to determine the relation between the teachers’women teaching skill and the learning outcomes of the students at Muhammadiyah junior high school Limbung, Bajeng District, Gowa Regency. This study applied quantitative descriptive research method. The population of the study was all of 3 teachers women and all students as many as 362 people. In addition, the sampeling technique in selecting the teacherswas Saturated sampling while the 34 samples from the students were selected using Random Samplin technique.. The instruments implemented in this study were questionnaires, interview guides, and documentation with inferential statistical analysis using Proudact Moment correlation techniques. The result of the research showed that the teaching skill of the teacher of Islamic education was 26,058 which was categorized as skillful, the result of students' learning outcome was 8,411 which was categorized as high, while the result of the data analysis obtained was r = 1.344. Hence, it was revealed that the relationship between the teaching skills of the teacher women of Islamic religious education and the learning outcome of the students at Muhammadiyah junior high school Limbung was categorized as very high.